Unearthed [book club bag] : a Jessica Cruz story - Rivera, Lilliam (DC Comics, 2021)
"Jessica Cruz has done everything right. She's a dedicated student, popular among her classmates, and has a loving family that has done everything they can to give her a better life in the United States. While Jessica is a part of the Deferred Action for Childhood Arrivals program, allowing her to go to school and live in the U.S., her parents are undocumented. Jessica usually worries for her parents, but her fears and anxiety escalate as a mayoral candidate with a strong anti-immigration stance runs for office. As the xenophobia in Coast City increases, Jessica begins to debate whether it's worth renewing her status to stay in the U.S., or if her family would be safer and better off moving back to Mexico. And despite her attempts to lean on her friends and family, she finds herself constantly visited by visions of Aztec gods, one pulling her towards hope and the other towards anger. But when her father is detained by I.C.E., Jessica finds herself being pulled into an abyss of fear. With her father gone and feeling helpless, Jessica must find her way out of her fears and ultimately become a voice for her community."--Amazon.com